The Effect of the Covid-19 Pandemic on Community Behavior in the Implementation of an Indonesian Healthy Program with a Family Approach (PIS-PK) in the Work Health Center Pekanbaru - Dhea Adellina Riyadi Dhea Adellina Riyadi; Novita Rany; Ahmad Hanafi; Mitra Mitra; Dedi Afandi (Jurnal Kesehatan Komunitas, 2023)
The Indonesian Healthy Program with a Family Approach (IHP-FA) is a program that aims to know real problems in the community, improve quality comprehensive services, and increase people to become members of the National Health Insurance. Based on the profile of the Health Center in 2020, there was a decrease in the implementation from 83.4% to 77.01%. The purpose of this study was to find out the effect of the COVID-19 pandemic on people's behavior in the implementation of the Indonesian Healthy Program with a family approach at the Health Center. This research method used a qualitative type with a phenomenology. Informants to 12 people. Data was collected by means of in-depth interviews, observation and document review. Data analysis used content analysis and triangulation to see the validity of the data. The results  the role of health workers here was very necessary in order to achieve the goals and achievements, but due to the pandemic, health workers were more focused on handling and stopping the COVID-19 spread. Can be concluded that pandemics COVID-19 effect the behavior of the people in the implementation. Suggested officers health more and promotion to and related to the implementation of pandemic the protocol COVID-19 according to health.